Pilot-Scale Investigation of Forward/Reverse Osmosis Hybrid System for Seawater Desalination Using Impaired Water from Steel Industry - Hanaa M. Ali; Hanaa Gadallah; Sahar S. Ali; Rania Sabry; A. G. Gadallah (International Journal of Chemical Engineering)
This paper was focused on the investigation of a forward osmosis- (FO-) reverse osmosis (RO) hybrid process to cotreat seawater and impaired water from steel industry. By using this hybrid process, seawater can be diluted before desalination, hence reducing the energy cost of desalination, and simultaneously contaminants present in the impaired water are prevented from migrating into the product water through the FO and RO membranes. The main objective of this work was to investigate on pilot-scale system the performance of the combined FO pretreatment and RO desalination hybrid system and specifically its effects on membrane fouling and overall solute rejection. Firstly, optimization of the pilot-scale FO process to obtain the most suitable and stable operating conditions for practical application was investigated. Secondly, pilot-scale RO process performance as a posttreatment to FO process was evaluated in terms of water flux and rejection. The results indicated that the salinity of seawater reduced from 35000 to 13000 mg/L after 3 hrs using FO system, while after 6 hrs it approached 10000 mg/L. Finally, FO/RO system was tested on continuous operation for 15 hrs and it was demonstrated that no pollutant was detected neither in draw solution nor in RO permeate after the end of operating time.